Xây dựng một thủ tục truyền số liệu song công - Châu, Nguyễn Hải (Journal of Computer Science and Cybernetics, 2016)
The paper presents the design and implementation of a full-duplex data communication protocol. The main purpose of the design is to build a basic tool for a network. In addition, the protocol can be used in point-to-point communication to increase the usage of transmission line in both two directions.